2012
DOI: 10.1021/bi301046b
|View full text |Cite
|
Sign up to set email alerts
|

By Increasing the Affinity of Heparin for Fibrin, Zn2+ Promotes the Formation of a Ternary Heparin–Thrombin–Fibrin Complex That Protects Thrombin from Inhibition by Antithrombin

Abstract: Heparin binds fibrin and, by bridging thrombin onto fibrin, promotes the formation of a ternary heparin-thrombin-fibrin complex that protects thrombin from inhibition by antithrombin. Because thrombin binds γ(A)/γ'-fibrin, a variant with an extended γ-chain, with higher affinity than the bulk γ(A)/γ(A)-fibrin, γ(A)/γ'-fibrin affords bound thrombin more protection from inhibition by antithrombin-heparin. We examined the effect of Zn(2+) on heparin-thrombin-fibrin complex formation because Zn(2+) modulates hepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…The importance of the heparin-fibrin interaction is highlighted by the fact that higher doses of heparin are needed to achieve a therapeutic anticoagulant response in patients with venous thromboembolism than in those with acute coronary syndrome; a phenomenon that has been attributed to the larger thrombus burden in patients with venous thrombosis (47). Recently, we demonstrated that Zn 2ϩ promotes ternary complex formation, thereby augmenting the protection of fibrinbound thrombin from inhibition by antithrombin (10). The current work shows that fibrinogen also compromises heparincatalyzed inhibition of factor Xa in the presence of Zn 2ϩ .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the heparin-fibrin interaction is highlighted by the fact that higher doses of heparin are needed to achieve a therapeutic anticoagulant response in patients with venous thromboembolism than in those with acute coronary syndrome; a phenomenon that has been attributed to the larger thrombus burden in patients with venous thrombosis (47). Recently, we demonstrated that Zn 2ϩ promotes ternary complex formation, thereby augmenting the protection of fibrinbound thrombin from inhibition by antithrombin (10). The current work shows that fibrinogen also compromises heparincatalyzed inhibition of factor Xa in the presence of Zn 2ϩ .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that Zn 2ϩ augments ternary heparin-thrombin-fibrin complex formation and increases the protection of thrombin from inhibition by antithrombin in the presence of fibrin (10). The 4-fold increase in the affinity of heparin for fibrin in the presence of Zn 2ϩ leads to a similar elevation in the apparent affinity of thrombin for fibrin.…”
mentioning
confidence: 95%
“…6,8 The gA/g9 sequence contains a thrombin binding site, which reduces thrombin inhibition by antithrombin and heparin cofactor II. 9 On the other hand, binding to fibrinogen gA/g9 reduces the availability of thrombin in the circulation, an effect previously described as antithrombin I. 10 We previously found reduced fibrinopeptide (Fp)B but normal FpA release from gA/g9 compared with gA/gA fibrin, leading to gA/g9 fibrin networks made of thinner fibers and increased branching.…”
mentioning
confidence: 98%
“…Although thrombin utilizes exosite 1 to bind to the E-domains of ␥ A -Fg and ␥Ј-Fg, the interaction of thrombin with the ␥Ј-chain is mediated by exosite 2, a negatively charged domain that lies opposite to exosite 1 and serves as the heparin binding site on thrombin. By simultaneously binding to the E-domain and the ␥Ј-chain via exosite 1 and exosite 2, respectively, thrombin forms a bivalent interaction with ␥Ј-Fg that heightens its affinity relative to the univalent interaction of thrombin with ␥ A -Fg and renders thrombin more resistant to inhibition by antithrombin and heparin cofactor II (9). The unique interaction of thrombin with ␥Ј-Fg not only attenuates the reactivity of the enzyme with its inhibitors, but also with its substrates, thereby reducing the activity and availability of thrombin.…”
mentioning
confidence: 99%